Comparative Analysis of the Implementation of Technology Trends, Pedagogy Trends and Education Trends of Science and Non-Science Program Students in Sulawesi - Patmasari, Andi; Ahmar, Dewi Satria; Anggreni, Afrillia; Azzajjad, Muhammad Fath; Ningsih, Purnama; Ahmar, Ansari Saleh (JOIV : International Journal on Informatics Visualization, 2024)
As a result of their increased exposure to technology, today's students are skilled users of a wide range of digital gadgets in their daily lives. To solve difficulties, they can freely access knowledge across a variety of digital platforms; this ability has to be included into contemporary learning principles. The purpose of this study is to investigate how lecturers might modify innovative teaching methods to better suit the needs of their students. 125 people participated in the survey that we did; 59 of them were from scientific programs and 66 were from non-science programs. The study used observation sheets, interview guides, and questionnaires. The questionnaire was split into two sections: one measured students' opinion of the technology and pedagogical innovations used by lecturers, and the other their reactions to the classroom and educational system. Before any data was collected, the validity and reliability of the instruments were confirmed. The findings showed that students had preferences for different types of technology. Students in scientific programs liked interactive platforms like Edmodo and Google Classroom, while students in other programs liked webinars and video conferences. Additionally, the study found a relationship between the educational trends that lecturers apply, pedagogical innovation, and the learning environment. The results of this study are anticipated to improve instructional practices in digital learning settings and provide a basis for policymaking in continuing education.